CVN‐AD Alzheimer's mice show premature reduction in neurovascular coupling in response to spreading depression and anoxia compared to aged controls. Issue 7 (3rd March 2021) - Turner, Dennis A.; Degan, Simone; Hoffmann, Ulrike; Galeffi, Francesca; Colton, Carol A.
Abstract: We compared the efficacy of neurovascular coupling and substrate supply in cerebral cortex during severe metabolic challenges in transgenic Alzheimer's [CVN‐AD] and control [C57Bl/6] mice, to evaluate the hypothesis that metabolic insufficiency is a critical component of degeneration leading to dementia. We analyzed cerebral blood flow and metabolic responses to spreading depression (induced by K + applied to the cortex) and anoxia across aging in CVN‐AD + C57Bl/6 genotypes. In the CVN‐AD genotype progression to histological and cognitive hallmarks of dementia is a stereotyped function of age. We correlated physiology and imaging of the cortex with the blood flow responses measured with laser doppler probes. The results show that spreading depression resulted in a hyperemic blood flow response that was dramatically reduced (24% in amplitude, 70% in area) in both middle‐aged and aged CVN‐AD mice compared to C57Bl/6 age‐matched controls. However, spreading depression amplitude and conduction velocity (≈6 mm/min) did not differ among groups. Anoxia (100% N2 ) showed significantly decreased (by 62%) reactive blood flow and autoregulation in aged AD‐CVN mice compared to aged control animals. Significantly reduced neurovascular coupling occurred prematurely with aging in CVN‐AD mice. Abbreviated physiological hyperemia and decreased resilience to anoxia may enhance early‐onset metabolic deficiency through decreased substrate supply to the brain. Metabolic deficiency may contribute significantly to the degeneration associated with dementia as a function of aging and regions of the brain involved.